Please explain it in detail
Attachments:
![](https://hi-static.z-dn.net/files/d24/e962eee16a4374591d8ab95580009a96.jpg)
Answers
Answered by
8
hii...
By cross-multiplication we get ,
=> 2x - a = x - b
=> 2x - x = -b + a
=> x = a - b
Hence, option A is correct.
_____________________________
hope this helps !
By cross-multiplication we get ,
=> 2x - a = x - b
=> 2x - x = -b + a
=> x = a - b
Hence, option A is correct.
_____________________________
hope this helps !
Similar questions
Social Sciences,
8 months ago
Physics,
8 months ago
Math,
1 year ago
English,
1 year ago
Math,
1 year ago